SURGICAL SITE INFECTIONS IN EMERGENCY ABDOMINAL SURGERIES - DR. P. R. BYAS; DR. SHYAM KUMAR DHAKAITA (International Journal of Pharma and Bio Sciences, 2014)
Abdominal surgeries are one of the most common surgeries performed as an emergency procedure. After these surgeries in the postoperative period, the surgical site infection is one of the common complications leading to superficial wound disruption or burst abdomen resulting in increased postoperative hospital stay. Later it may also results in incisional hernia formation. Here in this study our aim was to find out the infection rates in emergency abdominal surgeries. Methods- All the 395 patients admitted and operated for acute abdominal conditions in R. D. Gardi medical college as an emergency procedure from March 2009 to September 2012 were included in this study. All the patient characteristics were noted and studied .Use of prophylactic antibiotics, type of operation, intra operative findings, operative time all were recorded. In the post operative period, the wound was inspected regularly for signs of infection, later; the hospital stay was also recorded. Results – The mean age of the patients operated in emergency was 46 years. Male patients were 280 and females were 115 in number [Male: Female ratio-2.4] Out of 395 patients 74[18.73%] showed the signs of postoperative surgical site infection. The operative procedure in which the rate of infection was highest was emergency exploratory laparotomy for ileal perforation [44.44%], followed by laparotomy for gastric perforation[32%]. The average duration of operation was 2 hours and 10 minutes. The postoperative stay was ranging from 9 to 32 days. Discussion –The incidence of surgical site infection in the emergency abdominal surgeries done in our institute was more as compared to that given in the literature